Studi Arkeologi Eksperimental Teknik Pengeboran Gelang Batu dari Purbalingga - Priyatno Hadi Sulistyarto; Lilin Kumala Pratiwi; Aldhi Wahyu Pratama; Salma Fitri Kusumastuti; Indah Asikin Nurani; Sofwan Noerwidi; Tedy Setyadi; Andreyas Eko Atmojo; Slamet Widodo; Ghusnul Assa Fuadillah (Pusat Penelitian Arkeologi Nasional, 2021)
Abstract. The stone bracelet is a neolithic artifact crafted by drilling techniques. Traces of stone bracelet workshop activities in Central Java were found in Purbalingga, which is spread across the North Serayu Mountains between Kali Tungtunggunung and Kali Laban. This study is based on the previous research hypothesis, which states that the manufacture of stone bracelets is carried out by drilling techniques using bamboo wulung (Gigantochloa atroviolacea). This study aims to prove this hypothesis. An experimental archaeological approach by conducting drilling experiments using several drill bits: iron drills, masonry/concrete iron drills, iron drills for natural stone, and bamboo drills. Meanwhile, the abrasive materials used are water, river sand, and quartz sand. The analysis was carried out by comparing the morphological and morphometric traces of the workings between artifacts and experimental results, based on microscopic observations with a magnification of 20x to 200x. Compared to the other drilling bits and abrasive materials, the experimental study revealed that bamboo drill bits, with quartz-sand and water as additional gritty material, showed the closest similarity.